PELATIHAN PENGOLAHAN STATISTIK ASUHAN KESEHATAN DI RSI IBNU SINA ‘YARSI’ PADANG - Syamsul Kamal; Eni Mahyuni (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Statistics are a description of a situation that is expressed in numbers, where this number can be read and interpreted in later decision makers by the leadership of the hospital or company. Hospital statistics are statistics that use and process data sources from health services in hospitals to produce information, facts and knowledge related to health services in the hospital. Statistical data processing at RSI Ibnu Sina has not been running optimally because it has not been coordinated at the divisions in the hospital. The purpose of this service is for medical record staff to understand and know how to properly and correctly process health care statistics. The method used is to conduct training and explanation of health care statistics to medical record officers. This PKM uses the ZOOM Online application because in the current pandemic state it is not possible to carry out PKM directly. Prior to the implementation of the Health Care Statistical Processing training, a pretest was held where of the 60 registered participants who attended as many as 37 participants who attended, out of the 10 questions that were given the correct answer was 42.4% and after being given training and another postest was held with the same material the results is 56.49%, so there is an increase in results and it is expected that there will be further training to increase understanding of medical record staff.